Development and clinical application of grading and classification criteria of lumbar disc herniation. Issue 47 (November 2017) - Hao, Ding-Jun; Duan, Kun; Liu, Tuan-Jiang; Liu, Ji-Jun; Wang, Wen-Tao
Abstract : Abstract: This study aimed to develop new grading and classification criteria for lumbar disc herniation (LDH). First, from January 1993 to January 2003, we collected the detailed information of 1127 patients with LDH and, based on that information, developed a new grading classification termed the 6-score-V-type criteria wherein conservative treatment is recommended for patients with type I, II, or IIIA, surgical treatment is recommended for type IIIC, IV, and V, and 3 months of conservative followed by surgery if no improvements are obtained during the conservative treatment period is recommended for type IIIBe. The distribution of types among the 1, 127 patients was: type I (7.9%), type II (22.9%), type III (34.1%), type IV (22.2%), and type V (12.6%). Type III cases were subdivided into type IIIA (9.9%), type IIIB (13.3%), and IIIC (10.8%). Second, from February 2003 to December 2009, we treated a separate group of 1130 patients with LDH according to this 6-score-V-type classification rubric and monitored them for 24 months. Therapeutic efficacy was assessed in 1130 patients with a standard evaluation for leg pain. Overall, 85.3% of the patients in the first year and 84.1% in the second year had good or excellent response ratings. The inter-examiner reliability was 98%. Assignment of therapeutic protocols according to the 6-score-V-type classification yielded satisfactory outcomes, indicating that the 6-score-V-type criteria are straightforward and practical.